1965
DOI: 10.1039/tf9656101921
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen effect in the photochlorination of trichloroethylene

Abstract: The oxygen effect in the gas-phase photochlorination of trichloroethylene has been investigated at 363 and 403°K in a conventional kinetic apparatus and in a reaction cell combined with a rapid mass spectrometer. Once initiated by light at 4358& the chlorination in presence of oxygen proceeds further in the dark. This " after-effect " has been investigated under various experimental conditions. The results can be represented by a reaction mechanism comprising (i) formation and decomposition of a peroxidic radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

1967
1967
1976
1976

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 0 publications
3
8
0
Order By: Relevance
“…The reaction mechanism presented here is similar to that proposed earlier to account for the oxygen-effect on the photochlorinations of C2H, [l], C2HCI, [2] and C,HCI, [3]. At temperatures lower than 400"K, the behaviour of l,2-CzH4C1, is similar to that of ethane.…”
Section: Equation (Xiii) Holds For Reaction (3) Of Schema (Vi) Comsupporting
confidence: 63%
See 1 more Smart Citation
“…The reaction mechanism presented here is similar to that proposed earlier to account for the oxygen-effect on the photochlorinations of C2H, [l], C2HCI, [2] and C,HCI, [3]. At temperatures lower than 400"K, the behaviour of l,2-CzH4C1, is similar to that of ethane.…”
Section: Equation (Xiii) Holds For Reaction (3) Of Schema (Vi) Comsupporting
confidence: 63%
“…The rateequation for the oxygen-inhibited photochlorination of C2H6 [l] is very different from that observed for C,HC15 121, C2HC13 [3] and C,Cl, [2]. This can be explained by the fact that the removal of the alkyl chaincarriers Re by 0, is in equilibrium with the reverse reaction for highly chlorinated ethanes and ethylenes (R. = CHCl,CCI,-[4], CC13CC1,*) but not for ethane (R-= CH,CH2-).…”
Section: Introductionmentioning
confidence: 99%
“…To eliminate the contributions of the dark reactions, the observed light reaction rates were extrapolated to time zero using the procedure already described. [3][4][5] The influence of the oxygen pressure on the initial rates of chlorination and oxidation of CzC14 and C,HCl, at 353. 5 13) and ( 18)) ; for oxidation, eqn.…”
Section: (Ix) Withmentioning
confidence: 99%
“…2 shows that the dependence of the initial rate of oxidation vOx on the oxygen concentration is, however, of the same type, for both C2C14 and C2HC15. The dependence of initial chlorination and oxidation rates on the chlorine, tetrachloroethylene and pentachloroethane pressures and on the incident light intensity have been measured in the same way as for trichloroethylene [3][4][5] and are also of the same form for both compounds. The range of variation of experimental conditions is given in table 1.…”
Section: (Ix) Withmentioning
confidence: 99%
“…This type of free-radical reaction was demonstrated by Shenvood and Gunning [47] who studied the gas-phase reactions of vinyl radicals and their derivatives with N O at room temperature and found that the chlorovinyl radical formed by chlorine atom addition to acetylene yields, upon reaction with NO, the following products: HCN, CO, and HC1, viz., the compounds very close to those which the present authors assume to result from the decomposition of species formed by the reaction of chlorovinyl radical and 0 2 . Reactions ( 5 ) , (6), and (7) are unambiguous chain propagation reactions, while reactions (8) and (9) are the steps of deactivation of the activated radical CZHzC102 * on the molecules of chlorine and inert gas, respectively. Steady-state treatment applied to the suggested scheme of the branched-chain process represented by reactions (0)-( 1 1) yields the following dependence of the lower oxygen concentration limit on the concentration of reactants: Equation (I) is in qualitative agreement with the experimentally found dependences of the limiting concentration of oxygen on the concentrations of chlorine, acetylene (no dependence), and inert gas.…”
Section: Discussionmentioning
confidence: 99%